2008
DOI: 10.1097/gim.0b013e318161317c
|View full text |Cite
|
Sign up to set email alerts
|

Association study between interleukin 1β gene and epileptic disorders: a HuGe review and meta-analysis

Abstract: Previous studies have examined the association of a single nucleotide polymorphism at the promoter region of interleukin 1B (IL-1␤-511T) with temporal lobe epilepsy and febrile seizures susceptibility, but those studies have

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 51 publications
1
23
1
5
Order By: Relevance
“…However, it is also important to consider that periodontitis is a complex trait disease, in which several other periodontopathogens, viruses, immunoregulatory cytokines, and systemic modifying factors not considered in this investigation may also be involved in the modulation of IL-1␤ levels (17,26,45,48). Therefore, it is reasonable to expect that SNPs, even those proven to be functional like IL-1␤(3954), potentially play a significant but not major role in the disease outcome, as described for other pathologies (21,22,50). Indeed, even in experimental periodontitis in knockout mice, in which a given cytokine is completely absent, the disease severity is usually found to be partially, but not completely, increased or decreased (9,10,44).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, it is also important to consider that periodontitis is a complex trait disease, in which several other periodontopathogens, viruses, immunoregulatory cytokines, and systemic modifying factors not considered in this investigation may also be involved in the modulation of IL-1␤ levels (17,26,45,48). Therefore, it is reasonable to expect that SNPs, even those proven to be functional like IL-1␤(3954), potentially play a significant but not major role in the disease outcome, as described for other pathologies (21,22,50). Indeed, even in experimental periodontitis in knockout mice, in which a given cytokine is completely absent, the disease severity is usually found to be partially, but not completely, increased or decreased (9,10,44).…”
Section: Discussionmentioning
confidence: 94%
“…Accordingly, meta-analysis studies demonstrate that the observance of covariates is important to unravel the possible association of IL-1␤(3954) with different pathological conditions (17,21,22,42,48,50). However, it is also important to consider that periodontitis is a complex trait disease, in which several other periodontopathogens, viruses, immunoregulatory cytokines, and systemic modifying factors not considered in this investigation may also be involved in the modulation of IL-1␤ levels (17,26,45,48).…”
Section: Discussionmentioning
confidence: 98%
“…IL-1β augments calcium permeability of glutamate receptors [54] and the function of kinases (ceramide-induced Src-family of tyrosine kinases) enhancing seizures of many kinds [55]. Endogenous IL-1β contributes to the generation of experimental FS, and a mutation in the IL-1β gene promoter that results in higher levels of this cytokine has been reported in some individuals with FS and TLE [24,25]. Whereas some infections (especially human herpes virus 6) seem to be a strong provoker of FS [56], it is unknown if this augments levels of cytokines in a child's brain.…”
Section: How Are Fs Generated?mentioning
confidence: 99%
“…Increased susceptibility to the development of FS is now known to result from mutations of several genes, including sodium channels [14][15][16], GABA A receptors [17][18][19][20], and hyperpolarization-activated cyclic nucleotidegated (HCN) channels [21][22][23]. Other single gene mutations, such as in the interleukin (IL-1) gene promoter, have also been implicated in a vulnerability to FS or TLE [24,25] and interaction among several genes might increase the probability of developing FS in a given individual [26,27].…”
Section: Geneticsmentioning
confidence: 99%
“…Different polymorphisms have been described in the IL-1β gene, and at least two influence protein production, one located in the promoter region at position -511 (IL-1β-511) [7] and the other in exon 5 [8] . The IL-1β-511T single-nucleotide polymorphism (SNP) is associated with TLE [9,10] and susceptibility to FSs [11,12] . Peltola et al also found that carriers of the promoter -511T allele and lacking the IL-1Ra allele 2 have an increased susceptibility to develop therapy-resistant epilepsy [13] .…”
mentioning
confidence: 99%